Strategic urban health communication - Okigbo, Charles C. (Springer New York, 2014)
Strategic Urban Health Communication Charles C. Okigbo, editor     People are bombarded with messages continuously and sorting through them constantly. In this milieu, critical ideas about health promotion and illness prevention are forced to compete with distracting, conflicting, even contradictory information. To get vital messages through, communication must be effective, targeted, artful-in a word, strategic.   Strategic Urban Health Communication provides a road map for understanding strategy, enhancing strategic planning skills, and implementing strategic communication campaigns. Deftly written chapters link the art and science of strategic planning to world health goals such as reducing health inequities and eradicating diseases. Flexibility is at the heart of these cases, which span developed and developing countries, uses of traditional and digital media, and chronic and acute health challenges. And the contributors ground their dispatches in the larger context of health promotion, giving readers useful examples of thinking globally while working locally. Included in the coverage:   Urbanization, population, and health myths: addressing common misconceptions. Integrating HIV/family planning programs: opportunities for strategic communication. The role of sports in strategic health promotion in low-income areas. The Internet as a sex education tool: a case study from Thailand. Advertising and childhood obesity in China. Health communication strategies for sustainable development in a globalized world.   Balancing depth of understanding of audiences and methods of reaching them, Strategic Urban Health Communication is a forward-looking resource geared toward professionals and researchers in urban health, global health, and health communication.